The implementation of federal law no. 10.639/2003: the teaching of African history and Afro-Brazilian culture and its unfolding in the school context - Lacerda Campos, Leonardo (2024)
This study aims to discuss the mechanisms that contributed to the implementation of Law 10.639/2003 and its consequences in the school context, as well as to analyze the teaching practice. To meet the objective, we analyzed official documents, delved into the bibliographies that support this theme, especially in the studies of Gomes (2003; 2006; 2007; 2012), Gusmão (2012), Ramos (2003), Nascimento (2003), Silva (2003; 2007). This study showed that to the extent that there is the promotion of racial equality, respect for differences, social justice, added to the positive contents of African and Afro-Brazilian culture, advances are perceived in the fight against racism in the school context in three Brazilian municipalities: Porto Seguro – BA, Vitória da Conquista – BA and São Carlos – SP.